Transformation of Organic Waste Materials as H2O Gel and Its Influence on Growth of Maize (Zea mays L.). Issue 1 (2nd January 2022) - Tahir, Mukkram Ali; Akhtar, M. Shahbaz; Nakashima, Yoshitaka; Sabah, Noor Us; Hassan, Sayed Haseeb Ul
ABSTRACT: Water is an essential component for healthy plants and a limiting factor of global crop production. Recently, use of water absorbent compounds (nontoxic hydrocarbons) is rapidly increasing for optimum crop growth under water stress environment. These polymers absorb water and release it slowly as per crop requirement to mitigate water scarcity. This research study was carried out at College of Agriculture, University of Sargodha, Punjab, Pakistan, during year 2018. In this experiment, first, water absorbent gel was formulated from different organic wastes (waste activated sludge and rice husk) under controlled conditions (temperature 28 ± 2 °C and relative humidity 55 ± 5%) in the laboratory. Then, a pot experiment was conducted to evaluate its efficiency on maize. The experiment comprised three treatments (water gel at 0 (T1 ), 1.5% (T2 ) and 2.5% (T3 ) of total soil bulk mass, respectively, along with recommended nitrogen (N), phosphorus (P), and potassium (K) doses at 160, 80, and 60 kg ha −1, respectively, with 12 replications using completely randomized design. The crop was grown for 90 days after sowing. Exogenous application of water gel at 1.5% of total soil mass (150 g) along with recommended dose of NPK (T2 ) significantly (P ≤ 0.05) enhanced plant growth traits including plant height (120.58 cm), stem diameter (18.42 mm), shoot fresh (40.42 g), and dry biomass (21.25 g), root fresh (23.50 g), and dry biomass (6.75 g), and chlorophyll (8.65 mg g −1 leaf Fwt) and relative leaf water contents (75.10). The morphological parameters of maize were significantly affected by T2 with reference to T3 and control treatments. Yield and yield-related traits of maize were significantly enhanced at T2 . It is plausible to conclude that these eco-friendly super absorbent polymers (water gel) are capable to minimize the water deficiency to a great extent. Abbreviations: Relative water content (RWC); Shoot fresh weight (SFW); Shoot dry weight (SDW); Root fresh weight (RFW); Root dry weight (RDW); Chlorophyll (Chl); Germination percentage (%); Control (CK); Nitrogen (N); Phosphorus (P); Potassium (K); Hydrogel (HG)